Temperature-responsive reversibly-adhered solid-solid phase change energy storage film and preparation method thereof
A temperature-responsive reversibly adhesive solid-solid phase change energy storage film is created by reacting isocyanate and polyethylene glycol to form a polyurethane-based material, addressing leakage and adhesion issues, and is suitable for wearable and complex configurations.
Patent Information
- Application Number
- CN202411636564.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-03
AI Technical Summary
Existing phase change materials often suffer from leakage, environmental pollution, and low recycling efficiency, and lack adhesion, and are not suitable for wearable applications with complex configurations or flexibility.
A temperature-responsive reversibly adhesive solid-state phase change energy storage film is developed by reacting isocyanate and polyethylene glycol to create a polyurethane-based material with a soft segment phase change, which is mixed with waterborne polyurethane to form a flexible, reusable, and temperature-controlled adhesive film.
The film is flexible, reusable, and has temperature-controlled reversible adhesion, solving the leakage and adhesion issues of traditional phase change materials, and is suitable for wearable and complex configurations.
Smart Images

Figure CN119241883A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional polymer materials, and relates to a temperature-responsive reversibly adhered solid-solid phase-change energy storage film and a preparation method thereof. Background Art
[0002] Phase change materials (PCMs) can store or release thermal energy by changing their physical state and keep the temperature constant for a certain period of time. They have been widely used in many fields. At present, the most common phase change materials are solid-liquid phase change and solid-solid phase change. However, the phase change process of solid-liquid phase change materials is prone to leakage, environmental pollution, and low recycling efficiency, which affects the practicality of such phase change materials. In order to solve this problem, a variety of methods for preparing shape-stable composite phase change materials have been proposed. However, these composite PCMs are usually rigid in the solid state, lack adhesion, and cannot fit well on the surface of thermal devices, increasing the interface thermal resistance and installation difficulty. Traditional phase change materials have always been considered to be solids or large-volume liquids with classic melting and solidification behaviors, such as paraffin, fatty acids, polyols, and inorganic salt hydrates. However, these phase change materials have defects such as easy leakage of liquid phase, solid rigidity, corrosiveness, large volume change, and high packaging cost. Therefore, they are not suitable for wearable application scenarios with complex configurations or flexibility.
[0003] Phase change films have performed well in the field of energy storage. As a new application form of energy storage phase change materials (PCM), phase change films make it possible to use PCMs in highly flexible and space-constrained fields. Summary of the invention
[0004] In response to the problems existing in the prior art, the present invention provides a temperature-responsive reversibly adhesive solid-solid phase change energy storage film and a preparation method thereof. The solid-solid phase change polyurethane is prepared by reacting isocyanate and polyethylene glycol to solve the phase change leakage problem. The soft segment phase change of polyurethane is used to effectively improve the adhesion and fixed installation efficiency.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a temperature-responsive reversibly adhered solid-solid phase change energy storage film, comprising: Polyethylene glycol and isophorone diisocyanate are added to an organic solvent for prepolymerization reaction, 1,4-butanediol is added for chain extension reaction, trimethylolpropane tris(3-mercaptopropionic acid) is added for cross-linking reaction, and vacuum drying is performed to obtain a polyurethane-based solid-solid phase change material; The obtained polyurethane-based solid-solid phase change material is physically mixed with waterborne polyurethane and then dried to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage film.
[0006] Preferably, the mass ratio of the polyethylene glycol, isophorone diisocyanate, 1,4-butanediol, and trimethylolpropane tris(3-mercaptopropionate) is 3-18:1.33:0.19:0.24.
[0007] Preferably, the polyethylene glycol has a molecular weight of PEG1000, PEG2000, PEG-4000 or PEG-6000.
[0008] Preferably, the catalyst used in the prepolymerization reaction is dibutyltin dilaurate.
[0009] Preferably, the organic solvent is butanone.
[0010] Preferably, the mass ratio of the polyurethane-based solid-solid phase change material to the waterborne polyurethane is 10:1 to 10:5.
[0011] Preferably, before the polyurethane-based solid-solid phase change material is physically mixed with the waterborne polyurethane, the polyurethane-based solid-solid phase change material needs to be dissolved in a butanone solvent, wherein the solid content of the polyurethane-based solid-solid phase change material is 10% to 20%.
[0012] Preferably, the polyethylene glycol needs to be vacuum dried at 100° C.-120° C. for 2-5 hours before use.
[0013] Preferably, the prepolymerization reaction conditions are heating in an oil bath at 70-80° C. and stirring for 4 hours; The conditions of the cross-linking reaction are heating in an oil bath at 70-80°C with stirring for 3 hours; and the vacuum drying temperature is 80°C-100°C.
[0014] A temperature-responsive reversibly adhered solid-solid phase-change energy storage film is prepared based on the preparation method.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a temperature-responsive reversibly adhered solid-solid phase-change energy storage film and a preparation method thereof, wherein the main raw materials include polyethylene glycol, isophorone diisocyanate, trimethylolpropane tris(3-mercaptopropionic acid) ester, etc., and a polyurethane solid-solid phase-change material having a molecular structure of alternating soft segments and hard segments is prepared by a polymerization method including two steps of prepolymerization reaction and chain extension reaction. The soft segment part is a long chain structure of PEG, and the hard segment part is composed of IPDI. The synthesis process is divided into two steps: the first step is prepolymerization, that is, the terminal hydroxyl group (-OH) of PEG reacts chemically with the -NCO group of IPDI to generate a carbamate group (-NHCOO-), which connects the PEG soft chain and the hard segment to form a polyurethane structure with alternating soft segments and hard segments, and obtains a low molecular weight prepolymer with -NCO groups at both ends. The solvent in the reaction is butanone and the catalyst is DBDT; the second step is chain extension, adding a chain extender, that is, BDO, to the prepolymer obtained in the first step, and the hydroxyl groups on BDO react with the -NCO groups at both ends of the prepolymer to complete the chain extension. After the reaction is completed, a solid-solid phase change material is obtained; the third step is cross-linking, adding TMMP to the substance obtained in the second step to complete the cross-linking. After the reaction is completed, a polyurethane-based solid-solid phase change material with a cross-linked structure is obtained, and then it is physically blended with a water-based polyurethane, and naturally dried to obtain a solid-solid phase change film with flexibility and temperature-controlled reversible adhesion. The preparation process of the polyurethane-based solid-solid phase change material of the present invention is simple and easy to scale up, and the tensile properties and heat storage properties of the phase change film can be effectively regulated by adjusting the molecular weight of PEG. Compared with pure PEG, the composite phase change material film still does not leak when the PEG is heated to above the phase change temperature, indicating that the leakage problem of the phase change process of the phase change material has been solved.
[0016] Furthermore, the prepared phase change energy storage film is continuous and reusable, can be bent, compressed, and sheared at will, and has temperature-controlled reversible adhesion; the present invention can be widely used in the fields of batteries, construction, wearable electronic devices, etc.
[0017] Furthermore, the present invention introduces water-based polyurethane into phase change energy storage materials. This material has both solid-solid phase change energy storage function and water solubility. Compared with traditional polyurethane phase change energy storage materials, it has a wider range of applications and can achieve ideal effects without using or using less organic solvents. The water-based polyurethane phase change energy storage film does not produce harmful solvents and pollutants during production and use, and meets environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A synthetic route for preparing the temperature-controlled reversible adhesion solid-solid phase change material of the present invention; Figure 2 The morphology of the final phase change energy storage film sample obtained in Example 1-3; Figure 3This is a schematic diagram of the phase change energy storage film sample obtained in Example 3 that can be bent and folded arbitrarily; Figure 4 This is a schematic diagram of the phase change energy storage film sample obtained in Example 3 that can be cut into different sizes and shapes; Figure 5 The leakage performance test diagram of PEG6000 and the phase change membrane material obtained in Examples 1-3; Figure 6 This is a thermal performance test diagram of the phase change energy storage material film of Example 4; Figure 7 is the enthalpy thermal change diagram of the phase change energy storage material film of Example 4; Figure 8 The WPUPCM-1 membrane prepared in Example 4 was hot pressed at 100°C to determine its recyclability and plasticity; Fig. 9 This is a graph showing the adhesion test of the phase change film material shown in Example 4. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0020] The technical scheme of the present invention is a method for preparing a polyurethane-based solid-solid phase change material, which comprises: prepolymerizing a phase change energy storage material polyethylene glycol (PEG) with isophorone diisocyanate (IPDI), using dibutyltin dilaurate (DBDTL) as a catalyst, adding 1,4-butanediol (BDO) for a chain extension reaction, then adding trimethylolpropane tris(3-mercaptopropionate) (TMMP) for a cross-linking reaction, and drying the obtained material after the reaction is completed to obtain a novel polyurethane-based solid-solid phase change material.
[0021] The obtained polyurethane-based solid-solid phase change material is then physically blended with water-based polyurethane and naturally dried to obtain a solid-solid phase change film with flexibility and temperature-controlled reversible adhesion.
[0022] According to a preferred embodiment of the method for preparing a polyurethane-based solid-solid phase change material of the present invention, dibutyltin dilaurate (DBDTL) is added as a catalyst, 1,4-butanediol (BDO) is added as a chain extender, and trimethylolpropane tris(3-mercaptopropionate) (TMMP) is added as a crosslinking agent during the prepolymerization reaction.
[0023] The mass ratio of polyethylene glycol, isophorone diisocyanate, 1,4-butanediol and trimethylolpropane tris(3-mercaptopropionate) is 3~18:1.33:0.19:0.24.
[0024] Among them, the total amount of hydroxyl groups in BDO and thiol groups in TMMP is equivalent to the total amount of isocyanate groups in IPDI in the reactants; According to a preferred embodiment of the method for preparing a polyurethane-based solid-solid phase change material of the present invention, the phase change energy storage material polyethylene glycol is PEG1000, PEG2000, PEG-4000 or PEG-6000.
[0025] According to a preferred embodiment of the method for preparing a polyurethane-based solid-solid phase change material of the present invention, the polyurethane phase change energy storage material ethylene glycol should be vacuum dried at 100° C.-120° C. for 2-5 hours before the reaction.
[0026] According to a preferred embodiment of the method for preparing a polyurethane-based solid-solid phase change material of the present invention, the isophorone diisocyanate (IPDI), 1,4-butanediol (BDO) and trimethylolpropane tris(3-mercaptopropionate) (TMMP) are first dissolved in acetone solvent.
[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] Example 1, a method for preparing a temperature-controlled reversibly adhered solid-solid phase change energy storage material film, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 3 g of PEG-1000 at 120 °C under vacuum for 3 h; Step 1.2) Take a small glass bottle, weigh 0.02 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 20 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-1000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70 °C and stir for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0029] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG1000.
[0030] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-1000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 10% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:1; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0031] Example 2, a method for preparing a temperature-controlled reversibly adhered solid-solid phase change energy storage material film, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 6 g PEG-2000 at 120 °C under vacuum for 3 h; Step 1.2) Take a small glass bottle, weigh 0.03 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 25 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-2000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70°C with stirring for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0032] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG-2000.
[0033] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-2000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 15% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:1; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0034] Example 3, a method for preparing a novel polyurethane-based solid-solid phase change material, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 12 g of PEG-4000 at 120 °C under vacuum for 4 h; Step 1.2) Take a small glass bottle, weigh 0.04 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 30 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-4000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70°C with stirring for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0035] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG-4000.
[0036] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-4000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 20% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:1; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0037] Example 4, a method for preparing a novel polyurethane-based solid-solid phase change material, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 18 g of PEG-6000 at 120 °C under vacuum for 5 h; Step 1.2) Take a small glass bottle, weigh 0.05 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 35 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-6000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70 °C and stir for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0038] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG1000.
[0039] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-6000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 20% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:1; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0040] Example 5, a method for preparing a novel polyurethane-based solid-solid phase change material, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 18 g of PEG-6000 at 120 °C under vacuum for 5 h; Step 1.2) Take a small glass bottle, weigh 0.05 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 35 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-6000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70 °C and stir for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0041] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG1000.
[0042] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-6000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 20% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:3; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0043] Example 6, a method for preparing a novel polyurethane-based solid-solid phase change material, is carried out according to the following steps: Step 1) Preparation of polyurethane-based solid-solid phase change materials Step 1.1) Dry 18 g of PEG-6000 at 120 °C under vacuum for 3 h; Step 1.2) Take a small glass bottle, weigh 0.05 g of catalyst dibutyl dilaurate (DBDTL), weigh 1.33 g of IPDI, and measure 35 mL of butanone as solvent, mix well and add to the flask; Step 1.3) Add PEG-6000 prepared in step 1.1) into the flask and mix with the mixed solution, heat in an oil bath at 70 °C and stir for 4 h to complete the prepolymerization reaction; Step 1.4) Weigh 0.19 g BDO and 0.24 g TMMP into a glass bottle, extract 10 mL of butanone as solvent, mix well and add to the flask, heat and stir in an oil bath at 70 °C for 3 h.
[0044] Step 1.5) The phase change material obtained in the flask was then dried in a vacuum oven at 80°C for 5 h to obtain a polyurethane-based solid-solid phase change material prepared using PEG1000.
[0045] Step 2) Preparation of temperature-controlled reversible adhesion solid-solid phase change energy storage film Step 2.1) mixing the PEG-6000 polyurethane-based solid-solid phase change material prepared in step 1) with butanone at a solid content of 20% to prepare a mixed solution; Step 2.2) mixing the mixed solution of step 2.1) with waterborne polyurethane in a mass ratio of 10:5; Step 2.3) Pour the mixed solution into a polytetrafluoroethylene mold and dry it naturally to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage material film.
[0046] like Figure 1As shown, it is a synthetic route map for preparing a temperature-controlled reversible adhesion solid-solid phase change material of the present invention. The present invention prepares a polyurethane solid-solid phase change material having a molecular structure of soft segments and hard segments by a polymerization method comprising two steps of prepolymerization and chain extension reaction. The soft segment part is a long chain structure of PEG, and the hard segment part is composed of IPDI. The synthesis process is divided into two steps: the first step is prepolymerization, that is, the terminal hydroxyl group (-OH) of PEG reacts chemically with the -NCO group of IPDI to generate a carbamate group (-NHCOO-), which connects the PEG soft chain and the hard segment to form a polyurethane structure of soft segment-hard segment alternation, and obtains a low molecular weight prepolymer with -NCO groups at both ends. In the reaction, butanone is used as a solvent and DBDT is used as a catalyst; the second step is chain extension, and a chain extender, that is, BDO, is added to the prepolymer obtained in the first step. The hydroxyl groups on BDO react with the -NCO groups at both ends of the prepolymer to complete the chain extension. After the reaction is completed, a solid-solid phase change material is obtained; the third step is crosslinking, and TMMP is added to the substance obtained in the second step to complete the crosslinking. After the reaction is completed, a solid-solid phase change material with a cross-linked structure is obtained.
[0047] Figure 2 This is a morphology diagram of the final sample obtained in Example 3. It can be seen from the figure that the color of the PCM film is light white and transparent, and the overall shape is consistent. Figure 3 It can be seen that the film can be bent and folded arbitrarily, and the smaller the thickness, the more flexible the phase change material film. In addition, Figure 4 It can be seen that the phase change material film can be easily cut into shapes of different sizes.
[0048] like Figure 5 The leakage performance test diagram of the phase change film material obtained by PEG6000 and Examples 4-6 is shown. After the prepared phase change film is placed on a heating table at 80°C for 30 minutes, it can be seen that the phase change film maintains the initial state and the phase change material does not leak. This shows that the prepared phase change film material has good shape stability.
[0049] Figure 6 , Figure 7In order to test the thermal properties of the phase change energy storage material films of Examples 4-6, PEG6K was used to react to prepare the phase change material, and then the aqueous polyurethane was mixed in the proportion (phase change material: aqueous polyurethane = 10:1, 10:3, 10:5), and the prepared solid-solid phase change energy storage material film was subjected to DSC test. It can be seen that the melting enthalpy of the phase change film material prepared by Example 4: aqueous polyurethane = 10:1, the phase change material prepared by Example 5: aqueous polyurethane = 10:3, and the phase change material prepared by Example 6: aqueous polyurethane = 10:5 are 84.71, 74.82, and 65.97 J / g, respectively, and the crystallization enthalpy is 69.76, 59.84, and 52.58 J / g, respectively.
[0050] The polyurethane-based solid-solid phase change material prepared by the present invention is obtained by polymerization reaction of phase change energy storage material PEG with isophorone diisocyanate IPDI and 1,4-butanediol BDO and TMMP, and then physically blended into a water-based roll to prepare a phase change membrane material. It not only has the advantages of physical and chemical properties of general polymer materials, such as constant and adjustable temperature, but also has the advantages of high phase change enthalpy value, good thermal stability, low synthesis cost, and reprocessability. It can be widely used in the fields of thermal management of energy storage, batteries, etc., temperature control, building energy saving, etc.
[0051] like Figure 8 The WPUPCM-1 membrane prepared in Example 4 was hot pressed at 100°C to determine its recyclability and plasticity. The specific recycling process is as follows. The original WPUPCM-1 membrane specimen was cut into small pieces and recycled after hot pressing at 100°C and 10 MPa for 15 min. It can be seen that the recycled specimens maintained the same light yellow appearance as the original specimens.
[0052] like Fig. 9 The phase change film of Example 4 shown has good adhesion, and the adhesion decreases after the temperature reaches a certain value, and has good temperature-controlled reversible adhesion performance.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a temperature-responsive reversibly adhered solid-solid phase change energy storage film, characterized in that: include, Polyethylene glycol and isophorone diisocyanate are added to an organic solvent for prepolymerization reaction, 1,4-butanediol is added for chain extension reaction, trimethylolpropane tris(3-mercaptopropionic acid) is added for cross-linking reaction, and vacuum drying is performed to obtain a polyurethane-based solid-solid phase change material; The obtained polyurethane-based solid-solid phase change material is physically mixed with waterborne polyurethane and then dried to obtain a temperature-controlled reversibly adhered solid-solid phase change energy storage film.
2. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The mass ratio of the polyethylene glycol, isophorone diisocyanate, 1,4-butanediol and trimethylolpropane tris(3-mercaptopropionic acid) ester is 3-18:1.33:0.19:0.
24.
3. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The polyethylene glycol has a molecular weight of PEG1000, PEG2000, PEG-4000 or PEG-6000.
4. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The catalyst used in the prepolymerization reaction is dibutyltin dilaurate.
5. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The organic solvent is butanone.
6. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The mass ratio of the polyurethane-based solid-solid phase change material to the waterborne polyurethane is 10:1-10:
5.
7. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: Before the polyurethane-based solid-solid phase change material is physically mixed with the waterborne polyurethane, the polyurethane-based solid-solid phase change material needs to be dissolved in a butanone solvent, wherein the solid content of the polyurethane-based solid-solid phase change material is 10% to 20%.
8. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The polyethylene glycol needs to be vacuum dried at 100° C.-120° C. for 2-5 hours before use.
9. The method for preparing a temperature-responsive reversibly adhesive solid-solid phase change energy storage film according to claim 1, characterized in that: The prepolymerization reaction conditions are as follows: heating in an oil bath at 70-80°C with stirring for 4 hours; The conditions of the cross-linking reaction are heating in an oil bath at 70-80° C. with stirring for 3 hours; and the vacuum drying temperature is 80° C.-100° C.
10. A temperature-responsive reversibly adhesive solid-solid phase change energy storage film, prepared based on the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of waterborne polyurethane solid-solid phase change material
CN112266458A
Novel polyurethane-based solid-solid phase change material as well as preparation method and application thereof
CN114478974A
Recyclable high-strength scratch-resistant self-repairing transparent polyurethane film and preparation method thereof
CN115260446A
Process for preparing solvent-free aqueous polyurethane dispersion
US20170107319A1
Cited By
Solid-solid phase change diaphragm material with in-situ thermal management and high-temperature conductivity enhancement functions and preparation method of solid-solid phase change diaphragm material
CN121992579A